Kuat Tekan Bebas Tanah Lempung Terhadap Penambahan Kapur dan Abu Sekam Padi - Kurniawan, Reffanda; Adiguna, Adiguna; Sahadi, Wiran; Setiobudi, Agus (Universitas Muhammadiyah Palembang, 2025)
Clay soil often becomes a problem for buildings that stand on it. In this regard, various efforts have been made to treat soil with these properties, one of which is by using CaCO3 lime and rice husk ash. One alternative used to improve soil quality is stabilization.The aim objective this study is to use clay soil stabilization techniques. a mixture of CaCO3 lime and rice husk ash with variations of 8%, 10% and 12%, and a curing period of 7, 14 and 28 days. The land used in this research came from Village Maju Jaya, District Pemulutan Selatan, Ogan Ilir. To ascertain the soil's physical characteristics, tests were carried out on a mixture of CaCO3 lime and rice husk ash. These tests include sieve analysis, water content, specific gravity, atterberg limit, modified proctor, hydrometer, and unconfined compressive strength test. The test results show that a mixture of CaCO3 and chalk variations can enhance the soil's mechanical qualities. Each variation tested shows an increase in test value, as seen in the graph. With a 28-day period and a variance of 12%, the highest value obtained was 2.161.